(untitled) (Portuguese Journal of Family Medicine and General Practice, 2006)
Introduction: A balanced diet is extremely important during adolescence as it fulfils nutritional requirements during this stage, as well as it establishes and reinforces eating habits for the whole life. The aims of the study were: to characterize adolescents eating habits, to analyse healthy food consumed and to determine if there are differences in the eating habits of different sex and age group. Methodology: This is a crossectional study of 200 students aged 13, 14, 17 e 18 belonging to a school of Matosinhos. The sample was selected not randomly, rather by convenience, stratified for age groups. A self-questionnaire was applied. The eating habits (milk, bread, meat, fish, eggs, rice, potatoes, soup, vegetables and fruit) and the differences between different sex and age groups were identified. A 2 test was used to compare proportions, with a significance level of 0,05. Results: Average number of daily meals 3-4 in 62,0% of adolescents. Daily milk consumption of 46,0%, meat 37,4%, fish 17,1%, soup 40,1%, vegetables 10,6% and fruit 39,7%. Discussion and Conclusion: Adolescents eating habits proved to be inadequate and not much healthy. In contradiction with some studies, an association in terms of sex and age of most eating habits has not been confirmed.